2004
DOI: 10.1182/blood-2003-09-3047
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of P-selectin ligand expression in naive versus memory CD4+ T cells: evidence for epigenetic regulation of involved glycosyltransferase genes

Abstract: Lymphocytes are targeted to inflamed sites by specific "homing" and chemo-kine receptors. Most of them, including ligands for P-and E-selectin, are absent from naive CD4 T cells and become induced after activation and differentiation in effector/memory cells. Polarized effector cells are characterized by the rapid production of distinct cytokines upon restimulation. Their cytokine memory is in part controlled by epige-netic imprinting during differentiation. Here we ask whether a similar mechanism could regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 27 publications
(30 reference statements)
4
30
0
1
Order By: Relevance
“…Some of the migratory phenotypes become apparently permanently imprinted on differentiation 28,45 and allow a selective delivery of memory populations to specific compartments of the body ("homing"). How stable homing phenotypes are acquired and maintained in the progeny of T and B cells is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the migratory phenotypes become apparently permanently imprinted on differentiation 28,45 and allow a selective delivery of memory populations to specific compartments of the body ("homing"). How stable homing phenotypes are acquired and maintained in the progeny of T and B cells is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…19 Evidence has been provided in recent years that differentiation of T cells into distinct lineages with stable phenotypes and functions involves epigenetic regulation of critical effector molecules [20][21][22] or lineage-specific transcription factors, such as Foxp3 in Tregs. [23][24][25][26] Only few studies demonstrated that molecules involved in trafficking are subject to epigenetic regulation in T cells 27,28 or cancer cells. 29,30 In addition, a considerable plasticity in the expression of homing receptors has also been observed in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using selective in vitro methylation, we show that the activity of the minimal fut7 promoter is impaired by methylation. Further evidence for the critical role of DNA methylation in control of selectin ligand expression comes from our previous findings that showed 5-aza-deoxycytidine, a DNA methylation inhibitor, enhancing the expression of P-lig in in vitro cultures (15). However, it remains to be elucidated whether demethylation in the fut7 locus in T cells relies on inhibition of methylation on the newly generated DNA strain during cell division mediated by DNA methyltransferases or on active demethylation involving ten-eleven translocation proteins, which convert 5mC to 5-hydroxymethylcytosine.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that the induction of selectin ligands in CD4 + T cells requires cell division, which is considered a window for epigenetic changes. Moreover, artificial demethylation with 5-aza-deoxycytidine in T cell cultures increased P-lig expression, suggesting that DNA methylation controls selectin ligand expression in CD4 + T cells (15).…”
mentioning
confidence: 99%
“…FUT3 overexpression in gastric cells also depends on hypomethylation of its promoter [17]. A similar observation is reported in FUT7 expression [18]. Although increases in the fucosylation level and FUT4 expression were observed in MDA-MB-231 cells treated with a methyltransferase inhibitor, zebularine [19], it is unclear whether FUT4 expression level is directly correlated with the methylation status of the FUT4 promoter.…”
Section: Discussionmentioning
confidence: 61%